Generating qualified prospects to increase sales opportunities for a biotechnology start-up - Cea, Criselda (Animo Repository, 2023)
The discovery as a new material of graphene has presented exciting opportunities for start-up companies. Graphene, a revolutionary two-dimensional material holds an immense potential for numerous applications across various industries. However, one of the significant obstacles hindering the success of start-up in this field is the unclarity of who tomorrow's potential buyers could be, defined as qualified prospects. This research aims to identify and understand the underlying causes of the lack of qualified prospects and propose effective strategies to address the issues. This research employs different complementary approaches to explore the factors contributing to the lack of qualified prospects in a start-up company operating in the graphene market. The research phase, started with a market study, involved in-depth collaboration and interviews with the CEO and members of the company. The interviews aimed to identify the specific challenges faced by a company in attracting qualified prospects as a bottleneck of their sales. Based on the findings, this study proposed to explore different lead generation tools to identify the better fitting customers and so enhance the ability to attract qualified prospects. In cycle 1, we employed a “push” marketing method, in particular the LinkedIn Sales Navigator tool. In cycle 2, we have opted for a “pull” method by employing the LinkedIn Ad Campaign. By addressing the lack of qualified prospects, this research contributed to the sustainable growth of SF, our biotech start-up company, as we showed in the evaluation chapters. Generally speaking, the insights and recommendations presented in this study can guide start-ups in the B2B market in selecting effective tools for generating qualified prospects and scale sales up, ultimately bringing on the market their innovative products. Keywords: biotech start-ups, qualified prospects, lead generation tools, graphene market